1997
DOI: 10.1007/pl00005009
|View full text |Cite
|
Sign up to set email alerts
|

Palytoxin-induced increase in endothelial Ca2+ concentration in the rabbit aortic valve

Abstract: Palytoxin (PTX) is one of the most potent toxins isolated from marine coelenterates of the genus Palythoa. It induces depolarization in various types of cells by increasing the permeability for monovalent cations. It has been reported that PTX induces endothelium-dependent relaxation of vascular smooth muscle. In this study, we examined the effect of PTX on the cytosolic Ca2+ concentration ([Ca2+]i) in the endothelium of rabbit aortic valves loaded with fluorescent Ca2+ indicators, fura-PE3 or fluo-3. PTX (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…It has been reported that the elevation of cytosolic Ca 2+ induced by palytoxin is dependent on extracellular Ca 2+ [12,17,18,[34][35][36]. Our assays using neuroblastoma cells also indicated that palytoxin, as well as ostreocin-D, evoked Ca 2+ entry from the external medium.…”
Section: Discussionsupporting
confidence: 71%
“…It has been reported that the elevation of cytosolic Ca 2+ induced by palytoxin is dependent on extracellular Ca 2+ [12,17,18,[34][35][36]. Our assays using neuroblastoma cells also indicated that palytoxin, as well as ostreocin-D, evoked Ca 2+ entry from the external medium.…”
Section: Discussionsupporting
confidence: 71%
“…It is known that changes in the intracellular concentration of ions caused by palytoxin implicate Ca 2+ . In fact, previous investigations revealed that the palytoxin effect on cytosolic Ca 2+ is dependent on extracellular Ca 2+ (Frelin and Van Renterghem, 1995;Amano et al, 1997;Ishii et al, 1997;Satoh et al, 2003). Within this context, and taking into account that palytoxin administered intraperitoneally caused intestinal injuries in mice (Ito et al, 1996), it would be interesting to see the effect of palytoxin and ostreocin-D on the microfilament network of intestinal cells and also to study whether Ca 2+ movements are playing any role in this effect.…”
Section: Discussionmentioning
confidence: 98%
“…Our goal was therefore to investigate the effect of PTX-6, YTX, CTX-3C, MTX, palytoxin, ostreocin-D, Pbtx-3 and Pbtx-9 on the actin cytoskeleton of freshly isolated enterocytes. We selected carefully the concentration of each toxin, noting previous studies carried out in other cellular models by our laboratory and reported in the literature (Amano et al, 1997;De la Rosa et al, 2001;Leira et al, 2002;Alfonso et al, 2003;Louzao et al, 2004). In the case of ostreocin-D, an analogue of palytoxin, we used the same concentration as with I. R. Ares and others PTXs and YTXs are marine toxins originally associated with DSP.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether SOCCs are responsible for maintaining high [Ca 2+ ] i in striatal GABAergic neurons exhibiting spontaneous slow Ca 2+ oscillations, we first tested the contribution of Ca 2+influx from the extracellular space in striatal GABAergic neurons with and without slow Ca 2+ oscillations by quantifying the time constant of fluorescence quench (Figures 2A,B). More Mn 2+ entry from the extracellular space caused faster fluorescence quench (Amano et al, 1997;Uehara et al, 2002;Tu et al, 2009). The Fura-2 LR fluorescence quench was observed after MnCl 2 (50 µM) administration in the neurons with slow Ca 2+ oscillations ( Figure 2B).…”
Section: Involvement Of Soccs In Spontaneous Slow Ca 2+ Oscillationsmentioning
confidence: 99%
“…Mn 2+ can pass through opened Ca 2+ -permeable channels and quenches the Fura-2 LR fluorescence emission (Amano et al, 1997;Kikuta et al, 2015). Thus, to evaluate Ca 2+ influx from the extracellular space, the rate of the quench by Mn 2+ was quantified as ∆ F/F at 380 nm (Uehara et al, 2002;Tu et al, 2009;Kikuta et al, 2015).…”
Section: Mn 2+ Quench Experimentsmentioning
confidence: 99%